Comparative study of accounting standards between Singapore and the Peoples' Republic of China - Neo, Karn Nee (2008)
Singapore has been encouraging local firms to venture abroad, for example, PRC. Our research hopes to help users gain a better understanding of the accounting practices of PRC. Hence, the research seeks to identify the similiarities and differences in the two countries' accounting standards. The analysis is done on one set of financial statements selected from each country.